Stress memory gene FaHSP17.8-CII controls thermotolerance via remodeling PSII and ROS signaling in tall fescue. Issue 3 (2nd May 2021) - Bi, Aoyue; Wang, Tao; Wang, Guangyang; Zhang, Liang; Wassie, Misganaw; Amee, Maurice; Xu, Huawei; Hu, Zhengrong; Liu, Ao; Fu, Jinmin; Chen, Liang; Hu, Tao
Abstract: High temperature is the most limiting factor in the growth of cool-season turfgrass. To cope with high-temperature stress, grass often adopt a memory response by remembering one past recurring stress and preparing a quicker and more robust reaction to the next stress exposure. However, little is known about how stress memory genes regulate the thermomemory response in cool-season turfgrass. Here, we characterized a transcriptional memory gene, Fa-heat shock protein 17.8 Class II ( FaHSP17.8-CII ) in a cool-season turfgrass species, tall fescue ( Festuca arundinacea Schreb.). The thermomemory of FaHSP17.8-CII continued for more than 4 d and was associated with a high H3K4me3 level in tall fescue under heat stress (HS). Furthermore, heat acclimation or priming (ACC)-induced reactive oxygen species (ROS) accumulation and photosystem II (PSII) electron transport were memorable, and this memory response was controlled by FaHSP17.8-CII . In the fahsp17.8-CII mutant generated using CRISPR/Cas9, ACC+HS did not substantially block the ROS accumulation, the degeneration of chloroplast ultra-structure, and the inhibition of PSII activity compared with HS alone. However, overexpression of FaHSP17.8-CII in tall fescue reduced ROS accumulation and chloroplast ultra-structure damage, and improved chlorophyll content and PSII activity under ACC+HS compared with that HS alone. These findings unveil a FaHSP17.8-CII –PSII-ROS module regulating transcriptional memory to enhance thermotolerance in cool-season turfgrass. Abstract : A transcriptional memory gene is associated with high histone methylation levels and mediates thermotolerance by regulating photosystem II-reactive oxygen species signaling in cool-season turfgrass.